Optimization of printing parameters for self-lubricating polymeric materials fabricated via fused deposition modelling - Zhang, Peiyang; He, Feiyang; Khan, Muhammad (MDPI, 2025)
This study investigated the feasibility of fabricating self-lubrication material using fused deposition modelling (FDM) technology, focusing on the influence of printing parameters on tribological performance. Experiments were conducted using PA and ABS materials, with varying printing speed, infill density, and layer height across four levels. The research established regression equations and fitted curves to describe the relationship between printing parameters and the coefficient of friction (CoF). Validation experiments demonstrated the reliability of the models, with errors within 10%. The results indicate that reducing printing speed and increasing infill density enhance surface quality, with infill density exerting a more significant effect. The influence of layer height on surface quality depends on the printer characteristics, making precise quantification challenging. Additionally, this study confirms that resin-based samples produced via FDM exhibit self-lubricating potential. These findings contribute to the optimization of FDM-printed structures by balancing surface quality and tribological performance.
Keywords: 3D printing; self-lubricating; coefficient of friction; infill density; printing speed; 4014 Manufacturing Engineering; 40 Engineering; coefficient of friction; 34 Chemical sciences